2012
DOI: 10.1100/2012/567327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zearalenone on IL-2, IL-6, and IFN-γmRNA Levels in the Splenic Lymphocytes of Chickens

Abstract: Zearalenone (ZEN) is an estrogenic mycotoxin produced by severalFusariumspecies, which can contaminate food and feed. These compounds elicit a wide spectrum of toxic effects, including the capacity to alter normal immune function. In this study, the in vitro effects of the treatment of ConA-stimulated splenic lymphocytes with ZEN (0–25 μg/mL) were examined. ZEN modulates the expression of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
(26 reference statements)
0
23
0
2
Order By: Relevance
“…It is suggested that ZEA operates in male germ cells through the induction of oxidative stress causing the inhibition of glutathione-S-transferase (GST) [8,9]. http ZEA has also been shown to be immunotoxic [15] in different animal species [15,16]. In blood of weanling piglets, ZEA increased the inflammatory cytokine (tumor necrosis factor-alpha (TNF-a) and interleukin-1 beta (IL-1b) synthesis [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is suggested that ZEA operates in male germ cells through the induction of oxidative stress causing the inhibition of glutathione-S-transferase (GST) [8,9]. http ZEA has also been shown to be immunotoxic [15] in different animal species [15,16]. In blood of weanling piglets, ZEA increased the inflammatory cytokine (tumor necrosis factor-alpha (TNF-a) and interleukin-1 beta (IL-1b) synthesis [17].…”
Section: Introductionmentioning
confidence: 98%
“…In blood of weanling piglets, ZEA increased the inflammatory cytokine (tumor necrosis factor-alpha (TNF-a) and interleukin-1 beta (IL-1b) synthesis [17]. In chickens, ZEA presented potent effects on the expression of splenic lymphocyte cytokine interleukin-2 (IL-2) and interleukin-6 (IL-6) and interleukin-10 (IL-10) [15]. ZEA seems to work as both suppressor and inductor of the production of inflammatory cytokines [17].…”
Section: Introductionmentioning
confidence: 99%
“…RNA extraction, cDNA synthesis, and RT-PCR followed the method described in our previous study (Zhu et al, 2013). The primers and probes for the housekeeping β-actin gene used for sequencing were previously reported (Zhao et al, 2013;Wang et al, 2012;Hangalapura et al, 2006) and were synthesized by Invitrogen (Shanghai, China). The IL-2, IL-4, IL-6, IL-12β, IL-17, IFN-γ, and β-actin mRNA GenBank accession numbers are as follows: AY510091, AJ621249, NM204628, AJ564202, AY744450, DQ470471, and L08165, respectively.…”
mentioning
confidence: 99%
“…As the secondary metabolites of fungi, mycotoxins are of great importance in agriculture, food and feed production due to their frequent occurrence in toxicologically relevant concentrations in cereal grains. Moreover, mycotoxins cause serious health problems both in human and animal (Abbès et al, 2006;Goyarts et al, 2007;Wang, Deng, Xu, Peng, & Zuo, 2012).…”
Section: Introductionmentioning
confidence: 99%